St. Symeon of Thessalonika. The Liturgical Commentaries. Edited and translated by Steven Hawkes-Teeples - Wybrew, Hugh (The journal of theological studies, 2012)
St Symeon, canonized by the Greek Orthodox Church in 1981, was archbishop of Thessalonika from 1416 or 1417 until his death in 1429. The city was taken by the Ottoman Turks the following year. Among his writings are two commentaries on the Byzantine liturgy, The Explanation of the Divine Temple and On the Sacred Liturgy, the latter part of a much longer work, the Dialogue in Christ. To a large extent they complement one another. The Explanation begins with an account of the economy of salvation and God’s revelation in the unchanging tradition of the Church. It goes on to explain the symbolic meaning of the church building and its furnishings and the significance of those officiating at the eucharist and their vestments.